2022
DOI: 10.3390/ijms23168951
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Trauma and DNA Methylation Profiles among African American Mothers and Children

Abstract: Potentially traumatic experiences have been associated with chronic diseases. Epigenetic mechanisms, including DNA methylation (DNAm), have been proposed as an explanation for this association. We examined the association of experiences of trauma with epigenome-wide DNAm among African American mothers (n = 236) and their children aged 3–5 years (n = 232; N = 500), using the Life Events Checklist-5 (LEC) and Traumatic Events Screening Inventory—Parent Report Revised (TESI-PRR). We identified no DNAm sites signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Compared with prenatal stress, the mechanisms of intergenerational transmission of the effects of preconceptional stress are less understood. Very few studies have investigated whether the effects of preconceptional traumatic experiences may be transmitted to later generations via changes in gene expression or DNA methylation [ 32 , 33 ]. One of the first studies examining the transmission of preconceptional trauma found lower blood FKBP prolyl isomerase 5 ( FKBP5 ) methylation in the children of Holocaust survivors compared to demographically comparable controls [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with prenatal stress, the mechanisms of intergenerational transmission of the effects of preconceptional stress are less understood. Very few studies have investigated whether the effects of preconceptional traumatic experiences may be transmitted to later generations via changes in gene expression or DNA methylation [ 32 , 33 ]. One of the first studies examining the transmission of preconceptional trauma found lower blood FKBP prolyl isomerase 5 ( FKBP5 ) methylation in the children of Holocaust survivors compared to demographically comparable controls [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide approaches are even rarer. One study examined child genome-wide DNA methylation patterns in saliva associated with a maternal trauma measure designed to screen for potentially traumatic events over the respondent’s lifetime (Life Events Checklist) [ 33 ]. Another study examined placental genome-wide DNA methylation differences associated with socioeconomic adversity, framed as a chronic source of stress throughout the mother’s life [ 26 ].…”
Section: Introductionmentioning
confidence: 99%